ANALISIS PEWARNA RHODAMIN B DAN PENGAWET NATRIUM BENZOAT PADA SAUS TOMAT YANG DIPERDAGANGKAN DI PASAR BESAR TRADISIONAL KOTA MALANG - Jannah, Orchidosia Zukhruffin; Suwita, Komang; Jayadi, Lukky (Jurnal Riset Kefarmasian Indonesia, 2021)
One type of food product that usually uses food additives in the form of coloring agents and preservatives is sauce. Tomato sauce is a pasta-shaped product with a distinctive aroma of tomatoes. The number of sauces containing hazardous substances circulating in the community because of the increasing number of emerging home industries that do not use the correct rules for making sauces. The purpose of this study is to analyze the content of Rodhamin B coloring agents and levels of preservative Sodium Benzoate in tomato sauce traded in the Traditional Market of Malang City. The design of this study is observational, which is to dig data about the quality of tomato sauce in Malang City's Big Market by looking at the content of Rhodamin B Content and Sodium Benzoate. From the results of the study note that all tomato sauce samples do not contain Rodhamin B, while 2 of the 3 samples contain sodium benzoate preservative which exceeds the maximum threshold of 1gr / kg. Therefore, the public must be careful in buying tomato sauce products or other products that can be harmful to health.